An Operational Evaluation of 3 Methoprene Larvicide Formulations for Use Against Mosquitoes in Catch Basins. (20th February 2018) - Harbison, Justin E; Runde, Amy B; Henry, Marlon; Hulsebosch, Bridget; Meresh, Alka; Johnson, Haley; Nasci, Roger S
Effectiveness in controlling mosquitoes in storm water catch basins in the North Shore Mosquito Abatement District (northeastern Cook County, Illinois) was determined for 3 formulations of methoprene-based larvicides (Altosid XR 150-day Briquets, Altosid 30-day Pellets, Altosid 30-day Granules) in 2017 using a pass/fail evaluation criterion, in which emergence of a single adult from pupae collected from the basin constituted a control failure. Over the course of the 16-week study, basins receiving the 150-day briquets were treated once and basins receiving the pellet and granular formulations were treated every 4 weeks, with the first treatment occurring during the last week of May. Untreated basins were also observed for comparison with the treated basins. Over the course of the study, adult mosquitoes emerged from pupae collected in 94.2% of the untreated basins that contained pupae. All of the formulations evaluated in the study demonstrated some degree of control compared with the untreated basins, with pupae successfully emerging as adults in 64.6%, 55.5%, and 21.8% of samples from 150-day briquet, 30-day tablet, and 30-day pellet–treated basins that contained pupae, respectively. Pellets reapplied every 28 days provided significantly more effective control than the other formulations. The simple pass/fail criterion for evaluating control effectiveness proved to be a useful procedure for comparing effectiveness to untreated basins and among treatments.